2012
DOI: 10.1007/s12094-012-0928-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of annexin A3 playing in cancers

Abstract: Annexin family proteins are a well-known multigene family of Ca(2+)-regulated phospholipid- and membrane-binding proteins. As one of the annexin family genes/proteins, accumulated researches have begun to reveal that annexin A3 (Anxa3) exhibits important roles in tumor development, metastasis and drug resistance. The summarized research evidences in recent years indicate Anxa3 might specifically functionalize either as a tumor suppressor or as a tumor promoter candidate for different cancers depending on the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 23 publications
1
68
0
Order By: Relevance
“…However, different members of the Annexin family proteins are either up-or downregulated in cancer tissue, so different Annexins may perform different roles in specific types of cancer (5,6). It has been demonstrated that Annexin A1 is associated with esophageal cancer and is overexpressed in laryngeal carcinoma cells; it may therefore progressively migrate from the nucleus towards the membrane during laryngeal tumorigenesis (7).…”
Section: Introductionmentioning
confidence: 99%
“…However, different members of the Annexin family proteins are either up-or downregulated in cancer tissue, so different Annexins may perform different roles in specific types of cancer (5,6). It has been demonstrated that Annexin A1 is associated with esophageal cancer and is overexpressed in laryngeal carcinoma cells; it may therefore progressively migrate from the nucleus towards the membrane during laryngeal tumorigenesis (7).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that disorders of Annexin expression are indirectly linked to different human diseases, such as rheumatoid arthritis, lung cancer, and diabetes [24][25]. The expression level of Annexin is closely related to the proliferation, differentiation, and invasion/migration of tumors as well as the clinical stages of tumors [12,20], and therefore has recently become a hot spot in the tumor research field. Human Annexin A3 genes are dispersed throughout the genome on chromosomes 4 q13-q22, including the two main isoforms of 33 kD and 36 kD [20].…”
Section: Discussionmentioning
confidence: 99%
“…Human Annexin A3 genes are dispersed throughout the genome on chromosomes 4 q13-q22, including the two main isoforms of 33 kD and 36 kD [20]. Many studies have shown that changes in Annexin A3 expression have an important impact on the onset, development, drug resistance, and metastasis of tumors [12][13][14][15][16][17][18]26]. The expression of Annexin A3 in carcinoma tissues is also closely associated with cancer type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also increases the metastasis of lung adenocarcinoma and hepatocarcinoma. On the other hand, development of prostatic and renal carcinoma was observed with the down-regulation of annexin A3 [44].…”
Section: Annexin A3 and Cancermentioning
confidence: 99%